The effects of germacrone on lipopolysaccharide-induced acute lung injury in neonatal rats - An, J-F.; Sun, Y.; Zhang, Q-L.; Zhang, F-L.; Zhang, J-L. (Cellular and Molecular Biology, 2014)
Germacrone is one of the main bioactive components in the traditional Chinese medicine Rhizoma curcuma and has been shown to possess an anti-inï¬‚ammatory activity. Our present study aimed to investigate the protective effects of germacrone on lipopolysaccharide (LPS)-induced acute lung injury in neonatal rats. Results showed that germacrone treatment significantly decreased the expression of pro-inflammatory cytokines IL-6 and TNF-Î±. Meanwhile, the expression of anti-inflammatory mediators TGF-Î²1 and IL-10 was obviously increased following germacrone administration. The LPS-induced pathological changes in neonatal rats were also attenuated by germacrone treatment. In vitro, MTT and EdU incorporation assay indicated that germacrone administration significantly increased the A549 cell viabilities in a dose-dependent manner. Besides, flow cytometry and TUNEL analysis showed that the cell apoptosis rate was significantly reduced in a concentration-dependent manner after germacrone injection. At the molecular level, we found that germacrone treatment promoted the expression of claudin-4 both in vivo and in vitro as shown by real time PCR and western blot. Collectively, our study demonstrated that germacrone protected neonatal rats against LPS-induced ALI partially by modulation of claudin-4.